Pengaruh Sistem Informasi Keuangan dan Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan pada Badan Pengelolaan Keuangan Aset Daerah Kabupaten Bireuen - Muhammad Fajar; Jamaluddin; Umar Iskandar (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to determine and analyze the financial information system and human resources on the quality of financial reports at the Bireuen Regency Regional Financial Asset Management Agency. This research uses quantitative research. The population of this research is all employees at the Regional Asset Financial Management Agency of Bireuen Regency, namely 56 employees. The sampling method used is the total sampling method, where the existing population is used as the total sample size. Data was collected by filling out a questionnaire, then the data was processed quantitatively. Based on the results of research and data analysis, it can be concluded that the financial information system variable (X1) partially has a significant effect on the performance of employees of the Bireuen Regency Regional Financial Asset Management Agency with a significant value of 0.000. The human resources variable (X2) also partially has a significant effect on the performance of Bireuen Regency Regional Asset Financial Management employees with a significant value of 0.002. Furthermore, the financial information system variable (X1) and the human resources variable (X2) simultaneously have a significant effect on the quality of the financial reports of the Bireuen Regency Regional Financial Asset Management Agency with a significant value of 0.000.